2008
DOI: 10.3844/ajbbsp.2008.61.72
|View full text |Cite
|
Sign up to set email alerts
|

The Autistic Phenotype Exhibits a Remarkably Localized Modification of Brain Protein by Products of Free Radical-Induced Lipid Oxidation

Abstract: Abstract:Oxidative damage has been documented in the peripheral tissues of autism patients. In this study, we sought evidence of oxidative injury in autistic brain. Carboxyethyl pyrrole (CEP) and iso [4]levuglandin (iso[4]LG)E 2 -protein adducts, that are uniquely generated through peroxidation of docosahexaenoate and arachidonate-containing lipids respectively, and heme oxygenase-1 were detected immunocytochemically in cortical brain tissues and by ELISA in blood plasma. Significant immunoreactivity toward al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 56 publications
0
46
0
Order By: Relevance
“…This may contribute to the occurrence of lipid-derived protein modifications in the brain. Thus, we recently reported that, remarkably, localized CEP and iso [4]levuglandin E 2 -derived protein modifications, which appear as filaments in the cortical tissue, are a hallmark of the autistic brain (43). Of course, a low level of PUFAs can also result in little or no susceptibility to oxidative damage, as PUFAs are the targets of free radical-induced lipid oxidation.…”
Section: Polyunsaturated Phospholipids Promote the Oxidative Fragmentmentioning
confidence: 99%
“…This may contribute to the occurrence of lipid-derived protein modifications in the brain. Thus, we recently reported that, remarkably, localized CEP and iso [4]levuglandin E 2 -derived protein modifications, which appear as filaments in the cortical tissue, are a hallmark of the autistic brain (43). Of course, a low level of PUFAs can also result in little or no susceptibility to oxidative damage, as PUFAs are the targets of free radical-induced lipid oxidation.…”
Section: Polyunsaturated Phospholipids Promote the Oxidative Fragmentmentioning
confidence: 99%
“…Children born prematurely have significantly ( p = 0.008) elevated mean levels of blood plasma iso [4]LGE 2 -adduct immunoreactivity, 22.7 -5.9 nmol/ml (n = 6) compared with 15.3 -5.0 nmol/ml (n = 16) in children with no significant birth events (24). This suggests that chronic inflammation is a heretofore-unrecognized consequence of premature birth or postnatal treatment protocols that result in a failure to develop fully competent antioxidant defenses.…”
Section: Figmentioning
confidence: 94%
“…Recent studies with the postmortem brain samples from autism and control subjects have provided further evidence on increased oxidative stress in autism. Increased levels of lipid-derived oxidative protein modifi cations, i.e., carboxyethylpyrrole and iso [4]levuglandin E 2 -protein adducts, and heme-oxygenase-1 (an inducible antioxidant enzyme) have been reported in the autistic brain, primarily in the white matter (Evans et al, 2008). Sajdel-Sulkowska et al (2008) have reported elevated levels of 3-nitrotyrosine (a specifi c marker for oxidative damage to proteins) in the cerebella of subjects with autism.…”
Section: Oxidative Stress In Autismmentioning
confidence: 99%